2017
DOI: 10.1051/kmae/2017042
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater crayfish distribution update and maps for Greece: combining literature and citizen-science data

Abstract: -Crayfish are charismatic creatures of high interest to humans, among others playing key roles in freshwater ecosystems. Considering the significance of indigenous crayfish species (ICS) as well as the risks posed by non-indigenous crayfish species (NICS) that may dissemite a crayfish plague pathogen Aphanomyces astaci, astacological research has advanced particularly in Europe. In this context, crayfish distribution patterns are of fundamental importance. Focused on all crayfish established in the Greek wild,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
(43 reference statements)
0
23
0
Order By: Relevance
“…As for A. leptodactylus, the most robust European native species that shows some invasive characteristics (Holdich et al, 2009;Hudina et al, 2016;Perdikaris et al, 2017b), collected data indicated their spreading into new areas previously inhabited by A. astacus , and at the same time their disappearance due to NICS dispersal (this study, Hudina et al, 2013Hudina et al, , 2017Rebrina et al, 2015). Since A. leptodactylus is known to be moderately resistant to the pathogen A. astaci (Kokko et al, 2012;Svoboda et al, 2012), we may expect its further slow-paced disappearance in contact zones with NICS, mainly due to competitive exclusions (Hudina et al, 2016), and further spreading and replacement of other ICS in continental Croatia.…”
Section: Discussionmentioning
confidence: 99%
“…As for A. leptodactylus, the most robust European native species that shows some invasive characteristics (Holdich et al, 2009;Hudina et al, 2016;Perdikaris et al, 2017b), collected data indicated their spreading into new areas previously inhabited by A. astacus , and at the same time their disappearance due to NICS dispersal (this study, Hudina et al, 2013Hudina et al, , 2017Rebrina et al, 2015). Since A. leptodactylus is known to be moderately resistant to the pathogen A. astaci (Kokko et al, 2012;Svoboda et al, 2012), we may expect its further slow-paced disappearance in contact zones with NICS, mainly due to competitive exclusions (Hudina et al, 2016), and further spreading and replacement of other ICS in continental Croatia.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, citizen science studies show the potential to collect extensive data at low costs across large areas (Dickinson et al, 2010). For crayfish distribution, Perdikaris et al (2017) have shown that citizen science data could provide useful data on presence and distribution of species. In our project, we wanted to collect data on the so far badly known phenology of overland dispersal as well as new data on distribution of F. immunis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of this survey, countries with a coastline seem more focused on marine than freshwater environments. Citizen science initiatives on NNS are well developed in marine ecosystems in Greece (Perdikaris et al 2017, Zenetos 2017, Giovos et al 2019 and have begun in Albania (Tanduo et al 2020) and Turkey (Huseyinoglu et al 2021 The definition of NNS of Montenegro is regulated by policy acts and corresponds to the NNS definition stipulated in the policy acts of Croatia. However, in other Balkan countries, as in the EU Member States, there is no consistent definition of NNS (Boon et al 2020).…”
Section: Discussionmentioning
confidence: 99%